Hero Commemoration and State Legitimation in Post-Communist Vietnam —A case study of martyr Võ Thị Sáu (1933-1952)— - Tran, Thi (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2022)
This essay examined the public veneration of the heroic figure Võ Thị Sáu (1933–1952) and its relations to state legitimation in post-communist Vietnam. Through the case study of Sáu, the essay illuminated some characteristics of contemporary hero commemoration and the socio-political conditions that gave rise to these transformations. The goal was to demonstrate how communist fighters were reimagined into the embodiment of the revolutionary past and the moral high ground of the communists. These heroes became a medium for conflating national identity with state attachment, and for smoothing out post-communist ideological ruptures in state identity, hence making them valuable assets for the state in overcoming challenges against its leadership in the post-communist era.